Durable response to pembrolizumab in hepatic metastasis from colonic carcinoma with Lynch syndrome: a case report - Xue, Cheng; Zhu, Dongqing; Wang, Xin; Jiao, Lina; Lu, Yunhui; Zhang, Sanli; Lv, Jiayi; Cui, Linlin; Ruan, Mengna; Xu, Dechao; Liu, Qingyang; Feng, Yun; et al. (Frontiers in Immunology, 2024)
Pembrolizumab and other immunotherapies have become central in treating metastatic colon cancer, particularly effective in patients with mismatch repair deficiencies. We report a case involving a man who initially underwent radical surgery for sigmoid colon cancer on April 27, 2011, followed by hepatic tumor resection on September 21, 2017.Post-surgery, he received eight cycles of adjuvant chemotherapy with the CAPEOX regimen and was regularly monitored through CT and MRI scans. On August 24, 2022, liver metastases were detected, and he was diagnosed with Lynch syndrome (LS) due to germline mutation in the MSH2 and EPCAM genes. He commenced treatment with 200mg of pembrolizumab intravenously every three weeks on September 2, 2022, and demonstrated a sustained response. However, after 17 cycles, he developed a treatment related-treatment adverse event (TRAE) of pancreatic endocrine dysfunction, leading to type 1 diabetes, managed with subcutaneous insulin injections. After 30 cycles of treatment, no evidence of disease was observed. This case underscores the significant clinical benefits of first-line pembrolizumab in managing hepatic metastasis in colonic carcinoma associated with LS, despite the occurrence of TRAEs. It raises critical questions regarding the optimal duration of immunotherapy following a complete or partial response and whether treatment should be discontinued upon the emergency of TRAEs. Continued research and forthcoming clinical trials with checkpoint inhibitors are expected to refine treatment protocols for LS-associated carcinoma.